Cardiometabolic risk factors are affected by interaction between FADS1 rs174556 variant and dietary vegetable oils in patients with diabetes: a randomized controlled trial - Zahra Fallah; Azam Ahmadi Vasmehjani; Shiva Aghaei; Mojgan Amiri; Hamidreza Raeisi-Dekordi; Fatemeh Moghtaderi; Alireza Zimorovat; Ehsan Farashahi Yazd; Farzan Madadizadeh; Sayyed Saeid Khayyatzadeh; Amin Salehi-Abargouei (Scientific Reports)
Abstract FADS1 rs174556 polymorphism influences on dietary fats metabolism and type 2 diabetes (T2DM). This study aimed to compare the effect of three oils of sesame, canola and sesame-canola on cardio metabolic factors across genotypes of rs174556 variant in patients with type 2 of diabetes. This study was a randomized triple-blind three-way cross-over clinical trial. 95 Subjects with T2DM replaced their regular dietary oil with sesame oil, canola oil, or sesame-canola oil for three 9-week phases and completed the study. There were three anthropometric measurements, blood sampling and biochemical assessments at the beginning, middle, and at the end of each phase for assessments. Genotyping was conducted using the polymerase chain reaction-restriction fragment length polymorphism (PCR–RFLP) method. In the crude model, there was an interaction between consumed oils and rs174556 variant on serum concentration of Apolipoprotein A-I (ApoA-1). During intake of sesame oil, lower levels of triglycerides (TG) were observed in individuals with TT genotype compared to C allele carriers’ allele, which remained significant in adjusted models. Compared to C allele carrier’s, the people with TT genotype experienced significant increase and decrease in serum levels of HDL and TG, respectively in adjusted models. Also, the subjects who consumed sesame-canola oil had lower serum concentrations of fasting blood glucose than those who received sesame and canola oils, regardless of used oils and genotypes. FADS1 Gene variant (rs174556) might modify cardiometabolic changes following dietary vegetable oils. Larger longitudinal studies especially randomized clinical trials are needed to clarify these associations.